2011
DOI: 10.1016/j.jcrs.2010.11.009
|View full text |Cite
|
Sign up to set email alerts
|

Laser-assisted subepithelial keratectomy retreatment surgery

Abstract: Laser-assisted subepithelial keratectomy retreatment following prior LASEK, both without the use of MMC, provided good predictability, safety, efficacy, and stability outcomes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 43 publications
(48 reference statements)
0
6
0
Order By: Relevance
“…[6][7][8][9] Quality of vision may be largely governed by epithelial cover, which usually occurs within 3 to 7 days of surgery but may take as long as 2 weeks. 10 This may contribute to the high QoV scores in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8][9] Quality of vision may be largely governed by epithelial cover, which usually occurs within 3 to 7 days of surgery but may take as long as 2 weeks. 10 This may contribute to the high QoV scores in the early postoperative period.…”
Section: Discussionmentioning
confidence: 99%
“…argon laser) [ 5 ] resulting in protein denaturation. Other lasers operate by photoablation such as the excimer laser used in refractive surgery [ 6 , 7 ] and by photodisruption such as the neodymium: yttrium-aluminium-garent (Nd:YAG) laser [ 8 ] (Fig. 1 ).…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Sekundo and colleagues found that 95.6 % of eyes in their cohort were within ±1.00 D [ 2 ]. Reported predictability of LASIK ranges widely from 78.2 % up to 96.7 % [ 10 , 11 ] with enhancement procedures typically being performed with flap lift LASIK or surface ablation [ 12 , 13 ]. The higher rates of predictability anticipated with SMILE suggest that enhancement rates will be lower than with LASIK.…”
Section: Discussionmentioning
confidence: 99%